Manifestation of Prosocial and Antisocial Behavior in a Basketball Match - Saulius Šukys; Vaida Zakrasienė Stankevičiūtė; Edas Nickus; Edita Šukienė (Lithuanian Sports University, 2018)
Research background and hypothesis. The number of studies examining moral issues in sport has increased but we still lack research about actual behavior of athletes during the match. It was hypothesized that players and coaches' behavior would differ in relation with players' age, course and the final outcome of the match. Research aim was to explore the manifestation of observed prosocial and antisocial behaviors in a basketball match. Research methods. Data were collected using observation technique. 40 games were observed in the two age groups: 13-14 and 17-18-year-old players. Research results. Younger players more often than the older ones demonstrated respect to the referee (p = 0.05), but older players showed respect to opponents more often (p = 0.01). In the second half of the game players quarreled with referees more often than at the beginning of the game (p = 0.001). When the difference in the final outcome of the game was less, athletes were more often angry with each other (p = 0.001) and cursed more often (p = 0.034). Coaches working with younger players showed disrespect to them more often (p = 0.02). Discussion and conclusions. Research partly confirmed the hypothesis that younger basketball players more often demonstrated prosocial behavior during the game. Antisocial behaviors of players were more common in the second half of the match and when the difference in the final result was less. Research did not confirm the fact that coaches who worked with older players demonstrated more antisocial behavior and that such behavior was more common when there was less difference in the results of the match. Keywords: basketball players and coaches' behavior assessment, moral behavior in sport, players' age, course of the game, final outcome of the game.